2019
DOI: 10.1002/ejoc.201901055
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Direct ortho‐C–H Bond Sulfonylation and Halogenation of Phthalazine‐1,4‐diones

Abstract: The regio-and chemo-selective Pd-catalyzed C-H activation methods have been successfully reported for directed C-H sulfonation and halogenation of pyridazinedione with arylsulfonyl chlorides and N-halosuccinimide, respectively. These [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Solvent screening studies suggested toluene to be an inferior solvent for the model reaction, while acetonitrile, ethanol, t butanol, and dichloroethane did not initiate any substantial product formation (Table 1, entries [14][15][16][17][18]. Notably, the model reaction was not workable under nitrogen atmosphere, while only 38% of 3aa was obtained by performing the model reaction under air atmosphere (Table 1, entries 19-20).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
See 1 more Smart Citation
“…Solvent screening studies suggested toluene to be an inferior solvent for the model reaction, while acetonitrile, ethanol, t butanol, and dichloroethane did not initiate any substantial product formation (Table 1, entries [14][15][16][17][18]. Notably, the model reaction was not workable under nitrogen atmosphere, while only 38% of 3aa was obtained by performing the model reaction under air atmosphere (Table 1, entries 19-20).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…In contrast, the usage of K 2 CO 3 (2 equiv) afforded a mixture of C-arylated and C/N-diarylated products 3aa and 4aa in 15% and 32%, respectively (Table 1, entry 13). Solvent screening studies suggested toluene to be an inferior solvent for the model reaction, while acetonitrile, ethanol, tert-butanol, and 1,2-dichloroethane did not initiate any substantial product formation (Table 1, entries [14][15][16][17][18]. Notably, the model reaction was unsuccessful un-…”
mentioning
confidence: 99%
“…Pyridazinedione-directed C–H functionalization using Ir, Rh, and Ru catalysts has been reported by several groups since 2016. Dabiri and co-workers successfully developed a palladium-catalyzed pyridazinedione C–H sulfonylation (Scheme ). Phthalazine-1,4-diones reacted with arylsulfonyl chlorides to give the corresponding ortho -sulfonylated products when Pd­(OAc) 2 and K 2 CO 3 were employed as the catalyst and base, respectively. It is noteworthy that when K 2 CO 3 was replaced by K 2 S 2 O 8 , which was employed for the generation of arylsulfonyl radicals by Cui and Wu, the expected product was not obtained.…”
Section: Direct Arylsulfonylationmentioning
confidence: 99%
“…Following our interest on C–H functionalization of aromatic systems, a transition-metal-catalyzed C–H functionalization of 2-aryl phthalazinediones and 3-aryl-2 H -benzo­[ e ]­[1,2,4]­thiadiazine-1,1-dioxides with 2,3-diphenylcycloprop-2-en-1-ones is reported to generate highly rigid spiro-phthalazinediones and spirobenzo­[ e ]­[1,2,4]­thiadiazine-1,1-dioxides, respectively. To optimize the reaction conditions, several catalysts and additives were screened under different conditions (Table ).…”
mentioning
confidence: 99%
“…12 Recently, 2arylindazoles have successfully been functionalized with αdiazocarbonyl compounds, 13 2-alkynylanilines, 14 alkynyl triazenes, 15 1,2-disubstituted alkynes, 16 dioxazolones, 17 maleimides, etc. 18 Following our interest on C−H functionalization of aromatic systems, 19 a transition-metal-catalyzed C−H functionalization of 2-aryl phthalazinediones 20 and 3-aryl-2H-benzo[e] [1,2,4]thiadiazine-1,1-dioxides 21 with 2,3-diphenylcycloprop-2-en-1ones 22 is reported to generate highly rigid spiro-phthalazinediones and spirobenzo[e] [1,2,4] spectively. To optimize the reaction conditions, several catalysts and additives were screened under different conditions (Table 1).…”
mentioning
confidence: 99%